Effects of angiotensin II on the cerebral circulation: role of oxidative stress - De Silva, Travice M.; Faraci, Frank (Frontiers in Physiology, 2013)
Oxidative stress has emerged as a key component of many diseases that affect the vasculature. Oxidative stress is characterized as a cellular environment where the generation of oxidant molecules overwhelms endogenous anti-oxidant defense mechanisms. NADPH oxidases are a family of enzymes whose primary purpose is generation of reactive oxygen species (oxidant molecules) and therefore are likely to be key contributors to oxidative stress. Hypertension is associated with oxidative stress in the vasculature and is a major risk factor for stroke and cognitive abnormalities. Angiotensin II (Ang II) is the main effector peptide of the renin-angiotensin system (RAS) and plays a critical role in promoting oxidative stress in the vasculature. In the cerebral circulation, Ang II has been implicated in reactive oxygen species generation, alterations to vasomotor function, impaired neurovascular coupling, inflammation, and vascular remodeling. Furthermore, studies in humans have shown that cerebral blood flow is altered during hypertension and therapeutically targeting the RAS improves cerebral blood flow. Importantly, many of the aforementioned effects have been shown to be dependent on NADPH oxidases. Thus, Ang II, NADPH oxidases and oxidative stress are likely to play key roles in the pathogenesis of hypertension and associated cerebrovascular disease. This review will focus on our current understanding of the contribution of Ang II and NADPH oxidases to oxidative stress in the cerebral circulation.